History and morality - Bloxham, Donald 1973- (Oxford scholarship online, 2020)
Should historians make value judgements about the past? Many historians think not, but Donald Bloxham contends that it is legitimate, often unavoidable, and frequently important. 'History and Morality' illuminates how far tacit moral judgements infuse works of history, and how strange those histories would look if the judgements were removed